THE INFLUENCE OF EMPLOYEE PROFESSIONALISM AND COMPETENCE IN IMPROVING THE QUALITY OF EMPLOYEE SERVICE ONE STOP INTEGRATED SERVICES, KEMBANGAN DISTRICT, WEST JAKARTA ADMINISTRATIVE CITY - Rina Apriyanti; Farida Ruhana; Mansyur Ahmad (Jurnal Ilmu Pemerintahan Widya Praja, 2023)
Service is the most important aspect in public organizations and government. Some literature emphasizes that service quality can be improved through the professionalism and competence of employees. This study aims to analyze the effect of professionalism and employee competence on service quality at the One Stop Integrated Service, Kembangan District, West Jakarta Administrative City. This research method uses quantitative methods with multiple linear regression using SPSS. The results of the analysis show that the professionalism and competence of employees have a positive and significant effect on service quality. Furthermore, it was found that the most influential dimension of professionalism was effectiveness and the most influential dimension of employee competence was self-concept.